Genetically engineered crops: Opportunities, constraints, and food security at a glance of human health, environmental impact, and food quality - Dawkar, V.V., Chougale, A.D.; Barvkar, V. (Genetically Engineered Foods, 2017)
Genetic modification (GM) is an incredible technology and it will be among the top 10 technologies developed in the 20th century. People believe that GM technology will answer the future food demand and enable the world to feed millions of people; however, there are apprehensions about the impact of GM crops on human health, the environment, and food quality. Due to the controversy over GM crops, it is important to think about their economic and social effects. GM plants are likely to have increased nutrient levels, produce pharmaceuticals, and show resistance to disease, cold, and drought, and thus increase food security. Conversely, they may also lead to the emergence of new allergens. When thinking about food quality, these crops have the ability to generate more nutritious varieties, which may be of benefit to malnourished populations. However, with the exception of Golden Rice (which was developed to face vitamin A deficiency) achievements in this field are a long way off. These crops also have the potential to have a positive environmental impact as herbicide-tolerant plants can be cultivated on all types of land; however, this also brings about the possibility of generating herbicide-resistant weeds. Overall, GM crops can increase incomes for farmers and aid in drug production; however, care should be taken before releasing GM crops into the environment because once they are planted there will be no turning back.